1993
DOI: 10.1177/095632029300400605
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Resistance to an Inhibitor of HIV Proteinase (Ro 31-8959) Relative to Inhibitors of Reverse Transcriptase (AZT and TIBO)

Abstract: SummarySerial passage of cell-free human immunodeficiency virus type 1 (HIV-1) strain GB8 on CEM cells was carried out in the presence of increasing concentrations of the HIV proteinase inhibit~r Ro 31-8959 in parallel with representative revers~(tanscriptase (RT) inhibitors (AZT and the TIBO compo'und, R82150).ln all instances, a significant increase in the concentration of compound required to produce a 90% reduction of syncytium formation (ICgo) was found after seven to nine passages of virus. Reduced sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
11
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…Several of these have been recently tested in human clinical trials and demonstrated significant reductions in viral load (14,15). However, similar to results obtained with reverse transcriptase inhibitors (1), HIV variants with reduced sensitivity to these inhibitors have emerged in cell culture and in treated patients (14,(16)(17)(18)(19)(20)(21)(22)(23)(24). Resistance mutations have been mapped to HIV-1 protease substitutions R8Q/M461, M46F, and V321/ V821 for A-77003, 184V/V82F for AB-538, and G48V/L9OM for saquinavir (16,19,(21)(22)(23).…”
mentioning
confidence: 96%
“…Several of these have been recently tested in human clinical trials and demonstrated significant reductions in viral load (14,15). However, similar to results obtained with reverse transcriptase inhibitors (1), HIV variants with reduced sensitivity to these inhibitors have emerged in cell culture and in treated patients (14,(16)(17)(18)(19)(20)(21)(22)(23)(24). Resistance mutations have been mapped to HIV-1 protease substitutions R8Q/M461, M46F, and V321/ V821 for A-77003, 184V/V82F for AB-538, and G48V/L9OM for saquinavir (16,19,(21)(22)(23).…”
mentioning
confidence: 96%
“…These compounds offer interesting perspectives as candidate anti-HIV drugs, i.e. Ro 31-8959 is active against HIV-1 in cell culture at a 40 virions in HIV-1-infected individual^.^^,^^ Following oral treatment with L-735,524 or ABT-538, all patients showed an exponential decay of plasma viremia over the first two weeks, clearly attesting to the in vivo antiviral activity of these HIV protease inhibitors.Although virus resistance to HIV protease inhibitors is believed to arise more slowly than with RT inhibitors,180 HIV-1 resistance to the protease inhibitor Ro 31-8959 was obtained after only five passages of HIV-1 in vitro in the presence of the compound.181 Resistance to C2 symmetric inhibitors of HIV-1 protease has been described,ls2 and is due to Val -Ala mutation at position 82 of the protease. Substitution of Gln or Lys for Arg at position 8 of the protease183 leads to a marked resistance of HIV-1 to A-77003.…”
mentioning
confidence: 99%
“…Recently, a number of investigators have succeeded in selecting HIV type 1 (HIV-1) variants in vitro with reduced sensitivity to several protease inhibitors (3,6,8,13,15,23,27,28). Such work suggests that HIV-1 protease can sustain multiple mutations that interfere with inhibitor activity while maintaining protease function.…”
mentioning
confidence: 99%